A new approach for explosion accident prevention in chemical research laboratories at universities - Koji Fukuoka; Masao Furusho (Scientific Reports, 2022)
Abstract Over the years, many accidents have occurred during chemical experiments in laboratories around the world. However, the methods of investigating and analysing accidents that have occurred at universities have not been consolidated, and the lessons learned from these accidents have not been shared. In this study, accident investigation reports of explosions in chemistry laboratories at two universities were analysed with an analysis tool based on the software/hardware/environment/liveware (SHEL) model. As a result, university accidents were classified as epidemiological models, and it became clear that the contributing factors to the accidents, which were investigated and analysed using the SHEL model, can be used as learning experiences and therefore applied for the prevention of accidents at other universities. Universities around the world need to come together to formulate research and analysis methods, rules for creating accident reports, etc. and provide a place for sharing information that will enable them to make use of the lessons learned from all kinds of accidents.